Heat and Mass Transfer by Vapour in Freezing Soils - Assel Sarsembayeva; Askar Zhussupbekov; Philip E. F. Collins (Energies, 2022)
Vapour mass transfer is often underestimated when designing the bases for structures in frost susceptible soils. Intensive and long-term vapour transport may lead to excessive frost heaving and associated issues. A vapour transport model and the algorithm of its calculation is presented in this study based on the results of experimental freeze–thaw cycles of nine soil samples with varied density. The temperature field distribution, air voids volume and the energy comprising latent heat for the phase transition and heat extracted during the temperature drop are the main parameters for determining the vapour velocity and the amount of ice formed. According to the results, the average speed of vapour transport in frozen soils was about 0.4 m/h. The amount of ice built in 1 h during uniaxial freezing due to the saturated vapour pressure difference was 1.64 × 10−5–3.6 × 10−⁵ g/h in loose samples and 1.41 × 10−⁶ g/h to 5.61 × 10−⁷ g/h in dense samples of 10 cm diameter and 10 cm high sections. The results show that vapour mass transfer can increase the risk of ice growth and related problems.